2021
DOI: 10.18502/ijpa.v16i4.7863
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Toxoplasma gondii Infection Potentiates Parkinson’s Disease Course in Mice Model

Abstract: Background: Toxoplasma gondii is a neuroinvasive protozoa pathogen that could manipulate its intermediate host's behavior. However, the possible link between T. gondii infection and the development of neurodegenerative disorders such as Parkinson’s disease (PD) has been proposed, we tested the hypothesis that in chronic toxoplasmosis neuroinflammation, and molecular mediators potentiate behavioral-cognitive impairments in BALB/c mice with PD. Methods: To establish chronic toxoplasmosis by Tehran strain, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…We therefore investigated the effects of β-glucan on microgliosis in the PFC of mice infected with T. gondii Wh6. Using Iba-1 as the immunofluorescent marker of microglia, we found that T. gondii infection significantly increased the number of microglia in the PFC, while β-glucan was clearly observed to decrease the number of microglia (F (3,36) = 303.7, P < 0.0001; Fig. 4b).…”
Section: β-Glucan Suppressed Microglia Activation In the Pfc Of T Gon...mentioning
confidence: 90%
See 2 more Smart Citations
“…We therefore investigated the effects of β-glucan on microgliosis in the PFC of mice infected with T. gondii Wh6. Using Iba-1 as the immunofluorescent marker of microglia, we found that T. gondii infection significantly increased the number of microglia in the PFC, while β-glucan was clearly observed to decrease the number of microglia (F (3,36) = 303.7, P < 0.0001; Fig. 4b).…”
Section: β-Glucan Suppressed Microglia Activation In the Pfc Of T Gon...mentioning
confidence: 90%
“…Following our observation that β-glucan improved microglial and astrocyte activation, we examined the effects of β-glucan on pro-inflammatory cytokines. Using double immunofluorescent staining of Iba-1 and IL-6, we found that the average intensity of fluorescence in IL-6-positive (IL-6 + ) cells and the percentages of Iba1 + IL-6 + cells in Iba1 + cells in the TG group were significantly higher than those in the NC group, while β-glucan significantly inhibited these alternations (F (3,36) = 4495, P < 0.0001, Fig. 6b; F (3, 36) = 145.3, P < 0.0001, Fig.…”
Section: β-Glucan Restricted the Expression Of Pro-inflammatory Cytok...mentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on social and cultural habits, geographical factors, climate and transmission routes, the Seroprevalence of toxoplasmosis varies widely between different countries (10–80%) (Zarean et al 2017 ). On a global scale, T. gondii infection is thought to affect more than a billion people (Firouzeh et al 2021 ). Ingesting cat feces-contaminated food or eating tissue cysts from raw or undercooked meat are the two major ways that people get sick, so that is the second most important food-borne parasitic disease in Europe (Firouzeh et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…On a global scale, T. gondii infection is thought to affect more than a billion people (Firouzeh et al 2021 ). Ingesting cat feces-contaminated food or eating tissue cysts from raw or undercooked meat are the two major ways that people get sick, so that is the second most important food-borne parasitic disease in Europe (Firouzeh et al 2021 ). In those with immune deficiencies or immune breakdown, this protozoan is regarded as an opportunistic and potentially fatal parasite (Sina et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%